Estimating Potential Output with a Multivariate Filter. (IMF Working Papers; Working Paper, 2010)
This paper develops a simple model for measuring potential output that uses data on inflation, unemployment, and capacity utilization. We apply the model to 10 countries, in addition to the United States and the euro area. While there is a substantial amount of uncertainty around our estimates, we find that the financial crisis has resulted in a reduction in potential output.